Burden of disease and change in practice in critically ill infants with bronchiolitis. Issue 6 (1st June 2017) - Schlapbach, Luregn J.; Straney, Lahn; Gelbart, Ben; Alexander, Janet; Franklin, Donna; Beca, John; Whitty, Jennifer A.; Ganu, Subodh; Wilkins, Barry; Slater, Anthony; Croston, Elizabeth; Erickson, Simon; et al.
Bronchiolitis represents the most common cause of non-elective admission to paediatric intensive care units (ICUs). We assessed changes in admission rate, respiratory support, and outcomes of infants <24 months with bronchiolitis admitted to ICU between 2002 and 2014 in Australia and New Zealand. During the study period, bronchiolitis was responsible for 9628 (27.6%) of 34 829 non-elective ICU admissions. The estimated population-based ICU admission rate due to bronchiolitis increased by 11.76 per 100 000 each year (95% CI 8.11–15.41). The proportion of bronchiolitis patients requiring intubation decreased from 36.8% in 2002, to 10.8% in 2014 (adjusted OR 0.35, 95% CI 0.27–0.46), whilst a dramatic increase in high-flow nasal cannula therapy use to 72.6% was observed (p<0.001). We observed considerable variability in practice between units, with six-fold differences in risk-adjusted intubation rates that were not explained by ICU type, size, or major patient factors. Annual direct hospitalisation costs due to severe bronchiolitis increased to over USD30 million in 2014. We observed an increasing healthcare burden due to severe bronchiolitis, with a major change in practice in the management from invasive to non-invasive support that suggests thresholds to admittance of bronchiolitis patients to ICU have changed. Future studies should assess strategies for management of bronchiolitis outside ICUs. Changing thresholds to admit bronchiolitis patients to PICU have had a major impact on cost and resource utilisation http://ow.ly/AVA630a08rx